Coping strategies of COVID-19 recovered patients at the Ghana Infectious Disease Centre. - Esinam Aku Amedewonu; Genevieve Cecilia Aryeetey; Anthony Godi; Josephine Sackeyfio; Alfred Dickson Dai-Kosi; Thomas Akuetteh Ndanu (PLoS ONE)
Background The Coronavirus Disease (COVID-19) is a disease with diverse effects on multiple organ systems, leading to varying presentations and severe complications. As the pandemic progresses, the challenges faced by those who recovered from the disease evolved as various coping strategies were adopted post recovery. Aim This study investigated the coping strategies used by individuals recovering from COVID-19 to manage the physical, psychological, and social impacts of the disease. It further explored the factors influencing these strategies and their correlation with post-recovery quality of life. Methods This cross-sectional quantitative study involved 150 participants who attended the Ghana Infectious Disease Centre's post-COVID-19 review clinic between January and June 2021. Coping mechanisms were evaluated using the Brief-COPE questionnaire, which covers 28 strategies across three styles: Problem-focused coping, emotional-focused coping, and avoidant coping. Participants rated their coping strategies on a 4-point Likert scale. Analysis of variance was used to determine differences in use of coping strategies. Quality of life was assessed with the EuroQol Group Association five-domain, five-level questionnaire (EQ-5D-5L) and the EQ-VAS scale. Spearman correlation analyzed the relationship between coping strategies and quality of life. Results Majority of the study participants used problem-focused (2.71 ± 0.64 SD) type of coping strategy, followed by emotional-focused coping (2.32 ± 0.43 SD). The least strategy used was avoidant coping (1.57 ± 0.39 SD). Older participants, non-healthcare workers, and those with complications or persistent symptoms exhibited higher scores in avoidant and problem-focused coping. Those with persistent symptoms had higher emotional-focused coping scores. Better quality of life was associated with less reliance on all types of coping strategies. Conclusion Patients recovering from COVID-19 at the Ghana Infectious Disease Centre used positive coping mechanisms effectively. Key predictors of coping strategies included age, persistent symptoms, and complications. Improved quality of life is correlated with reduced use of coping strategies.